Mammalian Genome Recombineering: Yeast, Still a Helper Microorganism of Choice? - Mila Vrančić; Sandra Gregorić; Andrea Paravić Radičević; Krešimir Gjuračić (Food Technology and Biotechnology, 2008)
Functional studies of complex mammalian genomes have been revolutionized by the development of the recombineering methodology. Recombineering represents the sum of in vivo recombinant DNA techniques used for the production and manipulation of targeting vectors by the process of homologous recombination within the host microorganism. Although this methodology had initially been developed in yeast, the term recombineering was coined after successful introduction of similar techniques in bacterial cells. Since then, due to simplicity of amplification, manipulation and purification of mammalian targeting vectors, Escherichia coli has become the dominant helper microorganism in functional genomics studies. However, some types of experiments in functional genomics still employ yeast as a unique host for the manipulation of megabase-sized mammalian genomic regions.